Efficiency Estimates of Public Health Center II Facilities in Southwestern Uganda - Tindimwebwa, Kenneth; Kidane, Asmerom; Joel, Silas (Journal of Economics and Behavioral Studies, 2018)
The study estimates the efficiency of public health centre II (HCII) facilities in Southwestern Uganda. Specifically, it determines the level of technical efficiency (TE), scale efficiency (SE) and estimates the economic savings required to make inefficient public health facilities efficient. An output-oriented Data Envelopment Analysis (DEA) is employed in the estimation of TE and SE. It was found out that 73 % of the HCIIs were technically inefficient while 27% were technically efficient. Mean TE stood at 72.3% implying that an average HCII could potentially improve its efficiency by increasing its outputs by 27.7%. In addition, 77% of the facilities were SE implying that they obtained the most productive scale size given the input-output combination. 23% of the facilities were scaled inefficient implying that they have more input waste attributable to their size. There is great potential for economic savings shown by different magnitudes of input reductions and output augmentations required to make inefficient facilities efficient. The study has important policy implications. The health sector should embark on rigorous periodic research and development to enhance healthcare delivery efficiently. Since the health units are small, there is a need to augment their scale sizes and improve on their management practices so as to enhance their overall productivity and efficiency. Stakeholders should scale up efforts to attract, align skills with needs and improve retention and motivation of the health workforce. Holistic investment in resource inputs is essential. A comprehensive monitoring and evaluation plan with key verifiable indicators to monitor the overall health sector performance is required.